PEMBUATAN PEREKAT LIGNIN RESORSINOL FORMALDEHID DARI NATRIUM LIGNOSULFONAT TANDAN KOSONG KELAPA SAWIT (Jurnal Teknik Kimia USU, 2015)
Oil palm empty fruit bunchesn are waste from palm oil mill utilization is still limited. Lignin utilization of oil palm empty fruit bunhes made of natural adhesive manufacture. Making adhesive is carried out in several stages namely the manufacture of powder oil palm empty fruit bunches free extractives, lignin isolation, the manufacture of sodium lignosulfonate, sodium purification lignosulfonate and the manufacture of adhesive. Making the lignin resorcinol formaldehide adhesive is done by differences sodium lignosulfonate : resorcinol : formaldehyde mole ratio are ratio 1:1:1, ratio 1:1:2 and ratio 1:1:3. The results obtained from testing the appearance of the adhesive has a blackish brown color. pH of each ratio is ratio 1:1:1 11,2, ratio 1:1:2 11,4 and ratio 1:1:3 12,0. Adhesive densities are ration 1:1:1 1,2857, ratio 1:1:2 1,2119, and ratio 1:1:3 1,3097. Viscosities are ratio 1:1:1 108,83 cps, ratio 1:1:2 94,31 cps and ratio 1:1:3 129,92 cps. The rest of the evaporation are ratio 1:1:1 50,77%, ratio 1:1:2 42,35% and ratio 1:1:3 41,01%. Test results compared with standard phenol formaldehyde which is SNI 06-4567-1998 liquid phenol formaldehyde and result ratio 1:1:3 the best of another ratio .